Pollution removal capacities of aquatic plant species in the Datong Wetland Park in North China - Wang, Wei; Lv, Wujie; Li, Jiaying; Jiao, Xiang; Ma, Zhiqing (Journal of Environmental Engineering and Landscape Management, 2023)
The purification effect of a natural wetland landscape is often low when the focus is placed on the landscape effect. The effective combination of constructed wetland technology with landscape construction is challenging. Taking the Yuhe Wetland Park in Datong, Shanxi Province, China, as an example, the COD, phosphorus, and nitrogen removal capacities of aquatic plant species were determined, as well as the effects of the soil and the microbial communities. The highest COD and P removal capacity was observed for Typha orientalis Presl. which the purification rate reached 76.9% and 76.6%, and the highest N removal capacities were found for Scirpus validus Vahl., the rate of purification was 83.4%. Gram-negative bacteria were dominant.